Preparation process of automobile hub bearing blister tray
By using functional prepolymer slurry and microcapsules in the thermoforming trays for automotive wheel hub bearings, a gradient distribution of mechanical properties and multiple functions are achieved, solving the problems of cumbersome production processes and performance mismatch, and improving production efficiency and protection capabilities.
Patent Information
- Application Number
- CN202511320019.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-12-12
- Estimated Expiration
- 2045-09-16
AI Technical Summary
The existing production process for automotive wheel hub bearing blister trays is cumbersome, energy-intensive, and uses mismatched materials, making it impossible to provide proactive protection and quality traceability.
Functional prepolymer slurry is used, and a gradient distribution of mechanical properties is formed through digital light processing. Combined with corrosion-inhibiting, self-healing, and indicator microcapsules, in-situ polymerization and vacuum forming are achieved.
It shortens the production cycle, reduces energy consumption, matches material performance with structural function, and has active protection and quality traceability functions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of high polymer composite materials and packaging, in particular to a preparation process of an automobile hub bearing blister tray. BACKGROUND
[0002] As a common industrial packaging, blister tray is widely used in the circulation and transportation of precision parts, especially in the automobile manufacturing industry, for protecting high-precision and high-value parts such as hub bearings. At present, the mainstream manufacturing materials of such trays are petroleum-based thermoplastic plastics such as polyethylene terephthalate, polyvinyl chloride or polypropylene. The typical production process is as follows: first, a standard thickness sheet is prepared by extrusion or calendering process, then the sheet is stored and transported, and when needed, the whole sheet is heated to the softening temperature of the material, and finally the vacuum blister forming process is used to make it fit the mold to form the final tray structure. This way provides basic positioning and physical anti-collision protection for the parts.
[0003] However, with the increasing requirements for quality control and production efficiency of parts, the inherent limitations of such traditional blister trays and their manufacturing process have become increasingly prominent. The production process involves independent sheet manufacturing and subsequent secondary heating forming, with many links, which not only lengthens the production cycle, but also causes significant energy consumption due to the indiscriminate heating of the whole sheet. More importantly, since it is derived from a homogeneous plastic sheet, the finished tray has a single, undifferentiated mechanical property at all parts.
[0004] This homogeneity cannot meet the functional needs of different areas of the tray: for example, the load-bearing part needs high rigidity and strength, while the buckle or edge part needs good flexibility to facilitate taking and placing and to avoid breaking. This mismatch in mechanical properties often leads to waste of material or premature failure of local structures. In addition, the function of the traditional tray is limited to passive physical isolation, it cannot provide active protection or effective records for potential risk factors such as humidity changes and accidental impacts during transportation and storage, and once the packaging is damaged, its protection function is immediately lost, and it cannot provide any evidence for tracing the hidden damage suffered by the parts during the flow process. SUMMARY
[0005] The existing blister tray for packaging automobile hub bearings usually has a single function, mainly providing physical positioning and basic protection. Its manufacturing process usually involves multiple independent processes such as sheet extrusion, heating and softening, and vacuum blister forming, with a long process and high energy consumption. In addition, the traditional tray material does not have the ability to actively adjust the internal microenvironment of the packaging, nor can it record and indicate the occurrence of threshold value impact or humidity change during transportation or storage. When the product is rusted or the performance is reduced due to hidden damage, it is difficult to trace the cause.
[0006] Therefore, there is a need in the art to provide a new preparation process of an automobile wheel hub bearing blister tray, aiming to simplify the production process and integrate multiple intelligent functions into the final product.
[0007] To solve the above technical problems, the present application provides a preparation process of an automobile wheel hub bearing blister tray.
[0008] The preparation process comprises the following steps:
[0009] S1, preparing a functional prepolymer slurry: mixing a polymerizable bio-based prepolymer, functional microcapsules, and an initiator in a solvent to form a functional prepolymer slurry. A core technical feature is that the functional microcapsules have a polydopamine conductive shell layer and a functional capsule core.
[0010] S2, coating and film forming: applying the functional prepolymer slurry prepared in step S1 on a release substrate by blade coating or other uniform coating methods to form a liquid film with uniform thickness.
[0011] S3, in-situ polymerization: irradiating the liquid film formed in step S2 by an energy field. The energy field acts to simultaneously initiate in-situ polymerization of the bio-based prepolymer and evaporate the solvent. By applying the energy field non-uniformly and programmably, the polymerization degree in different areas of the film is made to differ, thereby forming a gel-state semi-finished product with a pre-set mechanical property gradient distribution.
[0012] S4, shaping and sizing: separating the gel-state semi-finished product attached to the release substrate from the release substrate and tightly fitting it to a mold with a wheel bearing contour. The fitting process is achieved by applying vacuum negative pressure. Then, the semi-finished product fitted with the mold is subjected to post-curing and cooling sizing treatment, and finally the blister tray with a three-dimensional structure is obtained.
[0013] In one specific technical solution of the present application, the functional prepolymer slurry is composed of the following components by weight:
[0014] Polymerizable bio-based prepolymer: 100 parts;
[0015] Functional microcapsules: 8.5-22 parts;
[0016] Initiator: 1-3 parts;
[0017] Solvent: 30-50 parts.
[0018] Further, the polymerizable bio-based prepolymer itself is a copolymer composed of the following components by weight:
[0019] Polylactic acid segment: 60-95 parts;
[0020] Polycaprolactone segment: 5-40 parts.
[0021] The prepolymer is a polylactic acid-polycaprolactone copolymer with terminal acrylate or methacrylate functional groups, with a number average molecular weight ranging from 2000 to 5000 g / mol.
[0022] The polymerizable bio-based prepolymer can be prepared by first, under anhydrous and anaerobic conditions, using stannous octoate as a catalyst, ring-opening copolymerization of lactide (LA) and epsilon-caprolactone (CL) monomers in a predetermined ratio to obtain a hydroxyl-terminated polylactic acid-polycaprolactone copolymer; then, the oligomer is dissolved in dichloromethane, and under the condition of triethylamine as an acid binding agent, methacryloyl chloride is added dropwise, and the reaction is continued after the reaction is raised to room temperature, and after the reaction is completed, the product is extracted, precipitated and dried to obtain the polylactic acid-polycaprolactone copolymer with terminal methacrylate functional groups.
[0023] In the present application, the functional microcapsules are selected from at least one of the following:
[0024] Corrosion inhibition microcapsules, whose functional core is a gas-phase corrosion inhibitor;
[0025] Self-repairing microcapsules, whose functional core is a two-component self-repairing agent;
[0026] Indicating microcapsules, whose functional core is a pressure-induced or moisture-induced color-changing dye.
[0027] In a preferred technical solution, the functional prepolymer slurry contains all three types of microcapsules described above, and the weight fractions are as follows, relative to 100 parts of bio-based prepolymer:
[0028] Corrosion inhibition microcapsules: 3-8 parts;
[0029] Self-repairing microcapsules: 5-12 parts;
[0030] Indicating microcapsules: 0.5-2 parts.
[0031] The preparation process of the functional microcapsules includes the following steps:
[0032] (a) Different types of functional cores are prepared into initial microcapsules by emulsion method or interfacial polymerization method;
[0033] (b) dispersing the different initial microcapsules obtained in step (a) in a weakly basic aqueous solution, and using the self-polymerization reaction of dopamine to form a layer of polydopamine conductive shell on the surface of the initial microcapsules, thereby obtaining a suspension containing functional microcapsules.
[0034] (c) performing solid-liquid separation on the suspension obtained in step (b), and performing washing and drying treatment on the separated solid product, to finally obtain a functional microcapsule powder that can be used to prepare slurry.
[0035] In one specific implementation of the S3 step, the energy field is generated by a digital light processing (DLP) module or a laser scanning galvanometer system. Different regions of the liquid film are irradiated with different energy densities by this system to form regions with different mechanical properties, specifically distinguished as:
[0036] High-strength region: the irradiation energy density is 80-150 mW / cm 2 , and the irradiation time is 5-15 s;
[0037] High flexibility region: the irradiation energy density is 20-50 mW / cm 2 , and the irradiation time is 2-8 s.
[0038] In one specific implementation of the S4 step, the process parameters of vacuum suction forming are as follows: the mold temperature is 60-80℃, and the vacuum degree is -70 to -95 kPa.
[0039] The present application provides a preparation process of an automobile hub bearing suction tray. It has the following beneficial effects:
[0040] 1. The process of the present application starts from a liquid functional prepolymer slurry, and directly generates a gel semi-finished product with specific mechanical properties through in-situ polymerization and vacuum suction forming. This process closely links the material polymerization and final product forming stages, eliminating the need for independent sheet extrusion, storage, and overall heating and softening before forming in traditional processes, thereby shortening the production cycle and reducing the corresponding equipment and energy consumption requirements.
[0041] 2、The present application composites the corrosion inhibition, self-repair and indication microcapsules as functional fillers in the bio-based polymer matrix, so that the tray is transformed from a passive physical support to an active functional system. The corrosion inhibition microcapsules can continuously release corrosion inhibition gas to protect the hub bearing, the self-repair microcapsules can repair the microcracks generated in the tray in use to maintain the structural integrity, and the indication microcapsules can make irreversible visual records on the physical impact or humidity environment exceeding the threshold, thereby providing direct evidence for product quality traceability.
[0042] 3、The present application utilizes the programmable control energy field such as digital light processing module or laser scanning galvanometer, and can accurately form high-strength areas and high-flexibility areas in the same structure of the tray according to the actual stress requirements of different parts. For example, high-energy irradiation is used to form a rigid structure with high cross-linking density at the part needing to bear the weight, and low-energy irradiation is used to form a flexible structure with low cross-linking density at the part needing to buckle or bend, so that the material performance and structural function are highly matched, and the overall reliability of the tray is improved. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present application will be described below in a clear and complete manner. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0044] The main raw materials and reagents used in the following examples and comparative examples are as follows, and the reagents not specifically described are commercially available analytical pure or higher grade products.
[0045] Monomer and prepolymer raw materials:
[0046] L-lactide: CAS No. 4511-42-6;
[0047] ε-caprolactone: CAS No. 502-44-3;
[0048] Methacryloyl chloride: CAS No. 920-46-7.
[0049] Catalyst and initiator:
[0050] Stannous octoate: CAS No. 301-10-0.
[0051] Functional capsule core raw materials:
[0052] Benzotriazole, CAS No. 95-14-7;
[0053] Bisphenol A diglycidyl ether: CAS No. 1675-54-3;
[0054] Ammonium chloride: CAS No.: 12125-02-9.
[0055] Shell and surface modification materials:
[0056] Dopamine hydrochloride: CAS No.: 62-31-7;
[0057] Tris(hydroxymethyl)aminomethane: CAS No.: 77-86-1;
[0058] Urea: CAS No.: 57-13-6.
[0059] Solvents, adjuvants and others:
[0060] Dichloromethane: CAS No.: 75-09-2;
[0061] Triethylamine: CAS No.: 121-44-8;
[0062] Ethyl acetate: CAS No.: 141-78-6;
[0063] Span 80: CAS No.: 1338-43-8;
[0064] Methanol: CAS No.: 67-56-1;
[0065] Calcium carbonate: CAS No.: 471-34-1;
[0066] Dodecane: CAS No.: 112-40-3;
[0067] Spiropyran: CAS No.: 1498-89-1.
[0068] Preparation Examples 1-4:
[0069] Preparation Example 1:
[0070] Preparation of polymerizable bio-based prepolymer:
[0071] Into a 500 mL three-necked flask equipped with a mechanical stirrer, a thermometer and a nitrogen inlet, 150 parts of L-lactide, 50 parts of ε-caprolactone and 0.2 parts of stannous octoate were sequentially added. The reaction system was heated to 140 °C under nitrogen protection, and stirred at this temperature for 6 hours. After the reaction was completed, the system was cooled to room temperature to obtain a hydroxyl-terminated polylactic acid-polycaprolactone copolymer. Subsequently, 200 mL of dichloromethane was added to the flask, and after the copolymer was completely dissolved, 20.2 parts of triethylamine was added under an ice-water bath. 22.1 parts of methacryloyl chloride was slowly added dropwise, and after the addition was completed, the ice-water bath was removed and the reaction was continued at room temperature for 12 hours. After the reaction was completed, the generated triethylamine hydrochloride solid was removed by suction filtration. The filtrate was washed with deionized water three times, then with saturated brine once, and then dried with anhydrous magnesium sulfate. After filtering to remove the drying agent, the solvent dichloromethane was removed by a rotary evaporator at 40 °C, and finally a clear viscous liquid product was obtained, which was a polymerizable bio-based prepolymer.
[0072] Preparation Example 2:
[0073] Preparation of corrosion inhibition microcapsules:
[0074] In a 250 mL beaker, 100 mL of deionized water, 5 parts of urea, 0.5 parts of Span 80 and 1 part of ammonium chloride were added. Stirring was carried out at a speed of 600 rpm until all the solids were completely dissolved. Subsequently, 20 parts of benzotriazole was added as the core material, and stirring was continued for 30 minutes to form a stable O / W emulsion. The pH value of the emulsion was adjusted to 2.5 with hydrochloric acid, and then 13.5 parts of 37% formaldehyde aqueous solution was added. The whole system was slowly heated to 60 °C, and reacted at this temperature for 3 hours to form initial microcapsules with urea-formaldehyde resin as the wall material. After the reaction was completed, it was naturally cooled to room temperature, and the product was collected by suction filtration and washed with deionized water and methanol alternately for several times, and then dried in a vacuum oven at 60 °C for 12 hours. 10 parts of the dried initial microcapsules were dispersed in 100 mL of 10 mM tris(hydroxymethyl)aminomethane buffer solution (pH = 8.5), and 1 part of dopamine hydrochloride was added. Stirring was carried out at room temperature for 24 hours in the dark to allow the dopamine to self-polymerize and coat on the surface of the microcapsules. After the reaction was completed, the product was collected by centrifugation, washed with deionized water until the supernatant was clear, and finally dried in a vacuum oven at 60 °C for 12 hours to obtain corrosion inhibition microcapsules coated with polydopamine on the surface.
[0075] Preparation Example 3:
[0076] Preparation of self-repairing microcapsules:
[0077] The preparation example provides self-repairing microcapsules with bisphenol A diglycidyl ether as the capsule core. The preparation method is basically the same as that of preparation example 2, except that the capsule core material is replaced by 25 parts of bisphenol A diglycidyl ether (DGEBA type epoxy resin) instead of 20 parts of benzotriazole. The dosages of all other raw materials, reaction conditions and post-treatment steps are exactly the same as those of preparation example 2. The final product is self-repairing microcapsules with polydopamine coated on the surface and epoxy resin as the capsule core.
[0078] Preparation example 4:
[0079] Preparation of indicating microcapsules:
[0080] The preparation example provides indicating microcapsules with a pressure-induced color-changing material as the capsule core. The preparation method is basically the same as that of preparation example 2, except that the capsule core material is replaced by 25 parts of a pressure-induced color-changing solution instead of 20 parts of benzotriazole, and the components of the pressure-induced color-changing solution are 99 parts by weight of dodecane and 1 part by weight of spiropyran. The dosages of all other raw materials, reaction conditions and post-treatment steps are exactly the same as those of preparation example 2. The final product is indicating microcapsules with polydopamine coated on the surface and a pressure-induced color-changing solution as the capsule core.
[0081] Example 1:
[0082] The embodiment provides a preparation process of an automobile hub bearing blister tray, and the specific steps are as follows:
[0083] S1, preparation of functional prepolymer slurry: weigh 100 parts of the polymerizable bio-based prepolymer prepared in preparation example 1 into a beaker, then add 30 parts of ethyl acetate, and mechanically stir at room temperature until the prepolymer is completely dissolved. Then, 3 parts of the corrosion inhibition microcapsules prepared in preparation example 2, 5 parts of the self-repairing microcapsules prepared in preparation example 3, 0.5 parts of the indicating microcapsules prepared in preparation example 4 and 1 part of TPO photoinitiator are added in sequence. The mixture is ultrasonically treated for 30 minutes to obtain a uniform and stable functional prepolymer slurry.
[0084] S2, film forming: pour the slurry prepared in step S1 on a clean PET release substrate, use a doctor blade to coat, control the wet film thickness to be 0.5 mm, and form a uniform liquid film.
[0085] S3, in-situ polymerization: place the release substrate with the liquid film into the light curing area of a digital light processing (DLP) molding device. Through a pre-set program, different areas of the liquid film are irradiated differently: for the positions where high strength areas are needed, an energy density of 80 mW / cm 2 is applied for 5 s; for the positions where high flexibility areas are needed, an energy density of 20 mW / cm 2at an energy density of 35 mW / cm2for 5 s. After irradiation is completed, a gelatinous semi-finished product adhering to the release substrate is obtained.
[0086] S4, molding and setting: the gelatinous semi-finished product is peeled off from the PET release substrate and immediately placed on a hub bearing metal mold preheated to 60°C. The vacuum system is started, and a vacuum degree of -70 kPa is applied to make the semi-finished product closely conform to the mold profile. This state is maintained and post-curing treatment is carried out in an oven at 80°C for 30 minutes, and then taken out and naturally cooled to room temperature to set, finally obtaining an automobile hub bearing blister tray.
[0087] Example 2:
[0088] This example provides a preparation process of an automobile hub bearing blister tray, which has basically the same steps as Example 1, except that:
[0089] In the S1 step, the weight fractions of each component are respectively: 100 parts of polymerizable bio-based prepolymer, 40 parts of ethyl acetate, 5.5 parts of corrosion inhibition microcapsules, 8.5 parts of self-repairing microcapsules, 1.25 parts of indicating microcapsules, and 2 parts of TPO photoinitiator.
[0090] In the S3 step, the irradiation parameters for the high-strength area are 115 mW / cm2for 10 s; and the irradiation parameters for the high-flexibility area are 35 mW / cm2for 5 s. 2 2 In the S3 step, the irradiation parameters for the high-strength area are 115 mW / cm2for 10 s; and the irradiation parameters for the high-flexibility area are 35 mW / cm2for 5 s.
[0091] In the S4 step, the mold preheating temperature is 70°C, and the vacuum degree is -82.5 kPa.
[0092] Example 3:
[0093] This example provides a preparation process of an automobile hub bearing blister tray, which has basically the same steps as Example 1, except that:
[0094] In the S1 step, the weight fractions of each component are respectively: 100 parts of polymerizable bio-based prepolymer, 40 parts of ethyl acetate, 5.5 parts of corrosion inhibition microcapsules, 8.5 parts of self-repairing microcapsules, 1.25 parts of indicating microcapsules, and 2 parts of TPO photoinitiator.
[0095] In the S3 step, the irradiation parameters for the high-strength area are 115 mW / cm2for 10 s; and the irradiation parameters for the high-flexibility area are 35 mW / cm2for 5 s. 2 2 In the S3 step, the irradiation parameters for the high-strength area are 115 mW / cm2for 10 s; and the irradiation parameters for the high-flexibility area are 35 mW / cm2for 5 s.
[0096] In the S4 step, the mold preheating temperature is 70°C, and the vacuum degree is -82.5 kPa.
[0097] Comparative Examples 1-3:
[0098] Comparative Example 1:
[0099] The present comparative example provides an automobile hub bearing blister tray prepared by using a traditional process. It uses a commercially available PET-G plastic sheet, which is softened by heating, and then directly formed on the hub bearing mold by using a vacuum blister forming machine. After cooling and setting, it is obtained. The tray does not contain the bio-based prepolymer and functional microcapsules of the present application, and the mechanical properties are uniform.
[0100] Comparative Example 2:
[0101] Compared with Example 2, the difference is that in the functional prepolymer slurry in step S1, no corrosion-inhibiting microcapsules, self-repairing microcapsules and indicating microcapsules are added, but 15.25 parts of calcium carbonate powder is used as a non-functional filler instead, and the rest is the same.
[0102] Comparative Example 3:
[0103] Compared with Example 2, the difference is that in the in-situ polymerization process of step S3, the liquid film is not differentially irradiated, but a single energy density of 75 mW / cm 2 is used to uniformly irradiate the entire film surface for 7.5 s, and the rest is the same.
[0104] Test Example 1-2
[0105] Test Example 1: Mechanical property gradient test
[0106] To verify the regulation effect of the preparation process on the mechanical properties of the blister tray, the samples prepared in Example 1, Example 2, Example 3 and Comparative Example 3 were tested for mechanical properties.
[0107] The specific test steps are as follows:
[0108] Sample preparation: From the blister trays prepared in Example 1, Example 2 and Example 3, test samples were cut out from the pre-set high-strength area and high-flexibility area, respectively. At the same time, from the tray with uniform mechanical properties prepared in Comparative Example 3, test samples were also cut out from the corresponding positions. All samples were cut into dumbbell shapes according to ASTM D638 standard, and the size of the test area was 25 mm in length and 4 mm in width.
[0109] Test equipment and conditions: A universal material testing machine was used to perform tensile testing at an ambient temperature of 23°C and a relative humidity of 50%. The tensile rate of the testing machine was set to 5 mm / min.
[0110] Data collection: Test 5 specimens for each zone and record the tensile strength (MPa) and elongation at break (%). Calculate the arithmetic mean of the 5 specimen test results for each zone as the final performance data.
[0111] Test results are recorded in the table below.
[0112] Table 1. Mechanical performance test data for different samples
[0113]
[0114] From the data in Table 1, it can be seen that the preparation processes of Examples 1, 2, and 3 all successfully formed zones with significant differences in mechanical properties within a single tray. Taking Example 2 as an example, the tensile strength of the high-strength zone (49.7 MPa) was more than 2.6 times that of the high- flexibility zone (18.5 MPa), while the elongation at break of the high- flexibility zone (115.8%) was more than 7.5 times that of the high-strength zone (15.3%). In contrast, Comparative Example 3, which used a uniform irradiation method, had no significant differences in mechanical properties throughout the sample, showing intermediate values between high strength and high flexibility (32.1 MPa tensile strength and 45.6% elongation at break).
[0115] The formation mechanism of the above performance gradient lies in the spatial selectivity of photon energy input in the in-situ polymerization step. Comparing Examples 1, 2, and 3, as the energy density and irradiation time applied to the high-strength zone increased (from 80 mW / cm 2 to 150 mW / cm 2 for 15 s), the tensile strength of this zone systematically increased from 41.2 MPa to 58.4 MPa. This is because higher total energy input causes a higher degree of photoinitiated crosslinking reaction of the acrylate functional groups at the end of the bio-based prepolymer, forming a more dense polymer network structure. This high-density network structure restricts the movement and sliding of high molecular chain segments under external force, thus macroscopically exhibiting an increase in material rigidity and strength, and a decrease in ductility.
[0116] Similarly, in the high-flexibility zone, lower energy input (from 20 mW / cm 2 to 50 mW / cm 2The irradiation 8s) forms a loose network with low crosslinking density, and the molecular chain segment has a larger activity space, thereby giving the material lower strength and higher elongation at break. The test results of this series prove that the technical solution can manufacture a structure with a preset mechanical property gradient distribution in a single component by accurately regulating the spatial distribution and dose of the input energy field. This method can give high strength performance to load-bearing structures and high flexibility to buckles and other parts, so as to accurately match the material performance and local functional requirements in space, thereby improving the utilization efficiency of the material and the overall reliability of the structure.
[0117] Test Example 2: Functional Test
[0118] In order to verify the multiple functions of the integrated blister tray, the samples prepared by Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were subjected to a functional comparison test.
[0119] The specific test steps are as follows:
[0120] Corrosion resistance test:
[0121] Take one complete tray prepared by Example 1, Example 2, Comparative Example 1 and Comparative Example 2. Place a polished Q235 steel sheet (50mm x 25mm x 2mm) in each tray, and then place the tray and the steel sheet together in a separate sealed container. Place all the sealed containers in a salt spray test chamber and perform a neutral salt spray test according to the ASTM B117 standard. The test conditions are: 5% NaCl solution, temperature 35°C. Every 12 hours, take out and observe and record the time when the first visible rust spot appears on the surface of the steel sheet.
[0122] Self-repairing performance test:
[0123] From the flat area of the trays prepared by Example 1, Example 2 and Comparative Example 2, sample strips with a size of 50mm x 10mm x 0.5mm were prepared. Since the PET-G material of Comparative Example 1 does not have a self-repairing design, this test is not performed. A surgical blade is used to make a 0.25mm deep cut in the center of each sample strip. The cut sample strip is left to stand for 24 hours in an environment of 23°C. Then, the tensile strength of the sample strip is tested using a universal material testing machine. At the same time, the initial tensile strength of the corresponding sample strip without cutting is tested. The self-repairing efficiency is calculated according to the following formula: Repairing efficiency (%) = (tensile strength of the repaired sample strip / initial tensile strength) x 100%.
[0124] State indicating performance test:
[0125] Pressure indication: samples were taken from the tray samples of Example 1, Example 2, Comparative Example 1 and Comparative Example 2, respectively. A static pressure of 2 MPa was applied to the samples using a flat head indenter with a diameter of 5 mm on a universal material testing machine, and the samples were held for 10 seconds before unloading. The color change in the pressure area was observed by naked eye.
[0126] Humidity indication: the tray samples of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were placed in a constant temperature and humidity chamber with a relative humidity of 95%, and the temperature was set to 30°C. The samples were placed in the chamber for 12 hours. After taking out, the color change of the samples was observed by naked eye.
[0127] The test results are recorded in the following table.
[0128] Table 2. Comparison of functional test results
[0129]
[0130] The test results in Table 2 show that the samples prepared in Example 1 and Example 2 both exhibit exact protection function. In terms of corrosion inhibition performance, the actual protection time exceeds 216 hours, which is significantly longer than that of Comparative Example 1 and Comparative Example 2 within 45 hours. The effect is due to the dispersed corrosion inhibition microcapsules in the tray substrate, which can continuously release gas phase corrosion inhibitor molecules, which form a dense physical adsorption layer on the surface of the metal part, thereby blocking the contact between the corrosion medium and the metal substrate. In terms of structural self-repairing ability, the samples of Example 1 and Example 2 can recover more than 80% of the initial strength after being damaged, and the mechanism is that when the tray substrate produces microcracks, the stress field at the crack tip will cause the self-repairing microcapsules on its path to break, and the repair agent inside the capsule core is released and flows into the crack gap to occur in situ polymerization reaction, thereby re-adhering and healing the two walls of the crack and restoring the mechanical bearing capacity of the material.
[0131] Table 3. Comparison of test results of state indication function
[0132]
[0133] The data in Table 3 show that the samples of Example 1 and Example 2 have the ability to respond and record specific external events, while the comparative sample does not. This function is achieved by compounding specific indicating microcapsules. When subjected to a specified pressure, part of the microcapsules containing pressure-induced color-changing dyes irreversibly break, and the dye molecules undergo structural changes after contacting the substrate environment, resulting in a visible color change in the pressure area. In a high humidity environment, the indicating microcapsules containing humidity-induced color-changing materials undergo hydration reaction or solvation effect due to the infiltration of water molecules, which also causes color change, thereby recording the over-standard humidity exposure event.
[0134] The series of test results jointly prove the technical effects of the technical scheme. By compounding a plurality of preset functional microcapsules in the biological-based prepolymer matrix and using an integrated polymerization-molding process, the tray of a single material successfully provides basic physical support while integrating multiple functions such as active corrosion inhibition, damage self-repair, and pressure and humidity state indication. The comparative example 1 cannot achieve the above-mentioned composite functions due to the limitation of the material itself, and the comparative example 2 cannot achieve the above-mentioned composite functions due to the lack of functional microcapsule components.
Claims
1. A manufacturing process for a thermoforming tray for automotive wheel hub bearings, characterized in that, Includes the following steps: S1. Preparation of functional prepolymer slurry: A polymerizable bio-based prepolymer, functional microcapsules and an initiator are mixed in a solvent to form a functional prepolymer slurry. The functional microcapsules have a polydopamine conductive shell and a functional core. The preparation steps of the functional microcapsules include: (a) Initial microcapsules loaded with different functional cores were prepared by emulsion method or interfacial polymerization method; (b) The initial microcapsules obtained in step (a) are dispersed in a weakly alkaline aqueous solution, and a polydopamine conductive shell is formed on the surface of the initial microcapsules by the self-polymerization reaction of dopamine, to obtain a suspension containing functional microcapsules. (c) The suspension obtained in step (b) is subjected to solid-liquid separation, and the separated solid product is washed and dried to finally obtain the functional microcapsules; S2, Coating to form a film: The functional prepolymer slurry prepared in step S1 is uniformly coated onto a release substrate to form a liquid film; S3. In-situ polymerization: The liquid film is irradiated by an energy field to induce in-situ polymerization of the bio-based prepolymer. Simultaneously, the solvent is evaporated and the bio-based prepolymer is irradiated in-situ to form a gel-state semi-finished product with a preset mechanical property gradient distribution. The energy field is generated by a digital light processing module or a laser scanning galvanometer system. By applying different energy densities to different areas of the liquid film, high-intensity areas and high-flexibility areas are formed. S4. Molding and Shaping: The gel-state semi-finished product is separated from the release substrate and placed on the wheel hub bearing mold. It is then conformed to the contour of the wheel hub bearing mold by vacuum negative pressure, followed by post-curing and cooling to finally obtain the blister tray.
2. The manufacturing process of a thermoforming tray for automotive wheel hub bearings according to claim 1, characterized in that, The bio-based prepolymer is made from the following components in parts by weight: Polylactic acid segments: 60-95 parts; Polycaprolactone segments: 5-40 parts; The functional prepolymer slurry comprises the following components in parts by weight: Bio-based prepolymer: 100 parts Functional microcapsules: 8.5-22 parts; Initiator: 1-3 parts; Solvent: 30-50 parts.
3. The manufacturing process of a thermoforming tray for automotive wheel hub bearings according to claim 1, characterized in that, The functional microcapsules include: Corrosion-inhibiting microcapsules, with a functional core consisting of a vapor-phase corrosion inhibitor; Self-healing microcapsules, with a functional core containing a two-component self-healing agent; The indicator microcapsules contain pressure-sensitive or moisture-sensitive color-changing dyes as their core.
4. The manufacturing process of a thermoforming tray for automotive wheel hub bearings according to claim 1, characterized in that, The irradiation energy density in the high-intensity region is 80-150 mW / cm². 2 The irradiation time is 5-15 seconds; the irradiation energy density of the highly flexible region is 20-50 mW / cm². 2 The irradiation time is 2-8 seconds.
5. The manufacturing process of a thermoforming tray for automotive wheel hub bearings according to claim 2, characterized in that, The functional microcapsules are present in the following weight parts: Corrosion-inhibiting microcapsules: 3-8 parts; Self-healing microcapsules: 5-12 portions; Indicator microcapsules: 0.5-2 parts.
6. The manufacturing process of a thermoforming tray for automotive wheel hub bearings according to claim 1, characterized in that, The conditions for the self-polymerization reaction of dopamine in step (b) are as follows: The reaction was carried out in a tris(hydroxymethyl)aminomethane buffer solution with a pH of 8.0-9.0 at 20-30°C for 8-16 hours.
7. The manufacturing process of a thermoforming tray for automotive wheel hub bearings according to claim 1, characterized in that, The polymerizable bio-based prepolymer is a polylactic acid-polycaprolactone copolymer oligomer containing terminal acrylate or methacrylate functional groups, with a number average molecular weight of 2000-5000 g / mol.
8. The manufacturing process of a thermoforming tray for automotive wheel hub bearings according to claim 1, characterized in that, The process parameters for vacuum forming in step S4 are: mold temperature of 60-80℃ and vacuum degree of -70 to -95kPa.
Citation Information
Patent Citations
Bio-based scratch-resistant blister tray and preparation method thereof
CN116731301A
Self-repairing easy-to-clean coating material as well as preparation method and application thereof
CN118879170A
Functional film, film-like curable composition, functional film production method, and article conveyance method
WO2021112132A1